THE HISTORICAL DEVELOPMENT OF JADE CULTURE IN CHINA - Тан, Чжунянь; Пашкевич, К. Л. (Art and Design, 2023)
The aim of the article is to analyze the historical process of transformation of applied methods used in jade carving, in order to investigate the paradigms of society's perception of jade and its forns, charactarize different historical and cultural epochs of China. Methodology. The research methodology is determined by a comprehensive study of the subject and includes: methods of analysis, synthesis, induction, method of structural and systemic analysis of sources, historical and comparative methods. Results. The degree of study of the topic in the scientific literature of Chinese authors was determined, scientific works outlining the historical development of jade products in China were analyzed. The main dynasties of China and the peculiarities of their culture are indicated, jade products and caarving evolution are studied. The characteristic features of local jade cultures, their differences and peculiarities are considered. Scientific novelty. The scientific novelty of the study consists of a complex approach to a jade artifacts of China as a complexed phenomena, formed along the cultural and historical evolutionary process. Practical significance. The materials of the article can be used when studying the topic of design in higher education and when writing scientific papers.